Understanding the Past-Present-Future Hydrogeologic System Through Numerical Groundwater Modeling of South Bengal Basin, India - Sikdar, Pradip Kumar; Banerjee, Sumanta; Chakraborty, Surajit (Frontiers in Water, 2022)
The quaternary hydrogeologic system of the South Bengal Basin in India with low natural topographic gradients, such as deltas and floodplains, is complex. This research elaborates the hydrogeologic system in and around the twin megacities of Kolkata and Howrah located on this complex delta of the South Bengal Basin and the rapid urbanization pattern during the past 30 years to understand the past, present (2016), and future (2030) behavior of the aquifer system and the advective flow paths of contaminants (wastewater, arsenic, and heavy metals) through hydrogeological simulations and field data. The groundwater model has been calibrated and validated by using the observed and simulated head. The root mean square error of the model is 1.07 m. The built-up area has increased from 142 to 243 km2 between 1985 and 2016, resulting in over-pumping of groundwater. About 93% of the available groundwater is abstracted, and as a result, the piezometric surface is declining at a rate of 13–37 cm/year and the groundwater trough in Kolkata is expanding at the rate of 8.60 km2/year. At places, the confined aquifer is behaving as an unconfined one, increasing the threat of land subsidence. The water quality is deteriorating in parts of Kolkata city where the groundwater is contaminated with wastewater, arsenic, and heavy metals, particularly in boroughs VIII and X. Contaminants from industrial sites may reach the strainer depth (100–120 m bgl) of pumping wells within a period of 20–25 years. The maximum simulated drawdown with respect to the predevelopment head is 22 m. If over-pumping continues, then simulation indicates that the head may drop by another 1.94–2.20 m by 2030. All this may endanger the health and well-being of millions of people living in the area in the near future.